TINJAUAN TEORI HUKUM PROGRESIF DALAM MELAKUKAN PENEMUAN HUKUM TERHADAP PENGGUSURAN DAN PERUSAKAN HUTAN ADAT - Lutfiah, Sausan Putri; Ratnawati, Elfrida (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This research discusses the implementation of progressive law theory in resolving issues of customary forest damaged by companies and their affiliates. Progressive law theory posits that law originates from the living norms of society, thus constantly evolving and adapting to the changing times. Enforcement of progressive law extends beyond written regulations to encompass the spirit and meaning of those regulations. The case of customary forest issues serves as the background for this study. The researcher evaluates the characteristics of progressive law, emphasizing that law serves humanity and must continue to evolve. This study also addresses issues in law enforcement that arise in specific cases, such as Decision No. 1983/K/Pdt/2015, which demonstrates inaccuracies in legal application. This research recommends legal innovation to ensure justice, legal certainty, and benefit for indigenous communities and the environment. The use of empirical studies in decision-making is considered crucial for ensuring progressive law enforcement. Based on progressive law theory, the researcher advocates for regulations acknowledging the damages to ecosystems and species caused by environmental destruction. Thus, this research contributes to understanding the implementation of progressive law theory in resolving complex legal issues, such as the destruction of customary forests by certain parties.